AB0154 WNT-BETA CATENIN PATHWAY MAY BE UPREGULATED IN ANKYLOSING SPONDYLITIS. (June 2019) - Magrey, Marina; Haqqi, Tariq; Singer, Nora; Breitman, Maya; Haghiac, Maricela
Abstract : Background: The Wnt–β-catenin pathway may play a critical role in new bone formation in ankylosing spondylitis. Wnt–β-catenin signaling depends primarily on the activity of glycogen synthase kinase-3β (GSK3β) that plays a key role in controlling β-catenin stability/degradation. It has been clearly established that phosphorylation of serine 9 in GSK3b correlates with the inhibition of its kinase activity and stabilization of β -catenin. Dickkopf-1 (DKK1) and sclerostin (SOST) are both upstream inhibitors of the Wnt/β-catenin pathway. Given that AS is associated with new bone formation we are interested in the molecular pathways that lead to this clinical phenotype Objectives: The objective of our studies was to test the hypothesis that "alterations in the Wnt–β-catenin activity may be a contributing factor in the pathogenesis of AS" Methods: 5 healthy donors and 12 patients (mean age 48 y.o., HLA-B27+ 70%) with AS based on New York classification criteria were enrolled. RNA was extracted from whole blood collected in PAX tubes following PreAnalytix kit protocol.Total mRNA was reverse transcribed using the high capacity cDNA Reverse Transcription Kit (Thermo Scientific) according to the manufacturer's instructions. TaqMan® Gene Expression Assays (IDT) were used to quantify mRNA levels of DKK1, SOST, and β-catenin. LightCycler480, and ΔΔ C T method were used to quantify the data (normalized to RPLP0(60S acidic ribosomal protein P0)). Protein lysates were prepared using NucleoSpin RNA/Protein kit (Takara) from PBMCs isolated from blood collected from the same 12 patients. Equal amounts of protein were loaded on 4–12% SDS gels and transferred to PVDF membranes. Membranes were blocked with 5% milk in TBST and probed at 4°C overnight with primary antibodies [rabbit anti-phosphoGSK3β (Ser9) (1:500; Cell Signaling, #9336), rabbit anti-GSK3β (1:1000; Cell Signaling, #9315), and mouse anti-β-actin (1:1000; Santa Cruz Biotechnologies, sc-47778)]. Appropriate HRP-conjugated secondary antibody was applied at room temperature for 1 hour. Immunoreactive protein bands were visualized using ECL (Pierce) and imaged with VisionWorks Image Acquisition and Analysis Software (Analytik Jena US, Upland, CA). β-actin was used as a loading control. Results: Compared to healthy controls the mRNA levels of DKK-1 and SOST were significantly lower in AS patients (p < 0.001), while the mRNA level of β-catenin was significantly higher in AS patients than in healthy controls (p < 0.05) (Fig 1 ). Compared to healthy controls, there was a several fold increase in the phosphorylation of GSK3b (Ser9) protein in the AS patient's sample. Conclusion: These data indicate that altered Wnt- β -Catenin activity may be contributing to the new bone formation in AS patients and thereby contributing to the disease pathogenesis and can be targeted for therpaeutic development. Disclosure of Interests: Marina Magrey Grant/research support from: M. Magrey received research funding from AbbVie and UCB for clinical trials, served as a consultant for Novartis, and was a member of advisory boards for Eli Lilly, Novartis, and UCB, Consultant for: M. Magrey received research funding from AbbVie and UCB for clinical trials, served as a consultant for Novartis, and was a member of advisory boards for Eli Lilly, Novartis, and UCB, Tariq Haqqi: None declared, Nora Singer: None declared, Maya Breitman: None declared, Maricela Haghiac: None declared